Chemical composition and selected quality characteristics of new types of precooked wheat and spelt pasta products. (30th March 2020) - Wójtowicz, Agnieszka; Oniszczuk, Anna; Kasprzak, Kamila; Olech, Marta; Mitrus, Marcin; Oniszczuk, Tomasz
Highlights: New types of precooked wheat and spelt pasta products have been developed. Extrusion-cooking applied for the treatment of wheat and spelt pasta allows to achieve instant products. Wholegrain pasta showed better nutritional composition and greater antioxidant potential. Pasta showed high gelatinization degree, compact structure and attractive quality. Abstract: New types of precooked pasta products have been developed based on refined and wholegrain wheat and spelt flours. The resulting dry pasta was then assessed for chemical composition, including amino acids composition, phenolics content, as well as antioxidant activity. The precooked pasta quality was also evaluated for starch gelatinization degree, physical properties, hardness, color profile of dry and hydrated pasta, and sensory characteristics. We found that the application of the extrusion-cooking technique for wheat and spelt pasta processing allows to achieve instant products with good nutritional characteristics and high degree of gelatinization, as well as attractive quality and sensory profiles. Microstructure showed compact and dense internal structure with visible bran particles if wholegrain flours were used. Wholegrain wheat and wholegrain spelt precooked pasta were characterized by better nutritional composition and greater antioxidant potential, but lower firmness and increased adhesiveness when compared with refined flours.